KAJIAN TENTANG PENDETEKSIAN SEL DARAH PUTIH DENGAN TEKNIK SEGMENTASI WATERSHED - David Reynaldo; Lina Lina (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
White Blood Cell (WBC) Detection is one of many proposed studies in medical field. There are many accomplish researches of this study using several methods such as detection using contour technique or color technique. Unfortunately, most of proposed research to detect WBC still using stained blood cells image to find out the existence of WBC. This staining process take so much time and various substances to do the process. In this paper, a method proposed to detect white blood cell in an unstained image of blood cell preparations using watershed segmentation technique. Firstly, the textures of WBC area are extracted using HSV colorspace. Then watershed segmentation is performed to segment red blood cells area, which is the image result leaving only texture areas. Then each texture area is determined whether the area is a WBC area or not. Experimental result shows the proposed method achieved an average accuracy around 45% success rate.